PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUASAN KONSUMEN BISNIS PROPERTI (Studi Kasus Perumahan Villa Gardenia Tipe 75 PT. Bintang Properti Panam - Pekanbaru) - Rudi Putra; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In the higher level of competition, companies must be able to face competitors offering similar products. Realizing that the company PT. Star property has been prepared by determining the location of strategic housing and promoting sales to meet the needs and challenges that are needed by the people of the city of Pekanbaru.This study aims to determine the location and sales promotion, in order to determine customer satisfaction, and to determine the influence of the location and promotion of consumer satisfaction at Villa Gardenia-type housing 75 at. Panam-star property Pekanbaru. This research is descriptive quantitative statistical calculations. The statistical analysis used in this research is multiple linear regression. The population in this study were residents of the Villa Gardenia type 75 150 households. The sample used in this study were taken 50% of the total population is defined by 75 respondents.The results showed that the sales location in a residential Villa Gardenia type 75 PT. Pekanbaru Panam-star property located in the category of